Implementasi Kebijakan Program Pembinaan Anak Putus Sekolah di UPT. Pelayanan Sosial Anak Remaja Tanjung Morawa - Indah Bertua Sianturi; Abdul Kadir; Irwan Nasution (Universitas Medan Area, 2022)
In an effort to reduce teenage dropouts, collaboration is needed from various parties, both from the government and the community. One of the efforts made is to provide social services. The social service aims to keep out of school teenagers getting education outside of school that can be used as provisions to obtain work so that they can meet their needs independently. The social services provided must of course have to be in accordance with the needs of teenagers dropping out of school. Social services th at can be provided are in the form of coaching for school dropouts through guidance. Guidance provided is religious mental guidance, social and physical guidance, skills guidance and Job Learning Practices (PBK). This research was conducted at the Technical Implementation Unit of Tanjung Morawa adolescent social services using qualitative descriptive research methods. While the source of the data in this study were employees at the UPT Sosisal Services for Adolescent Children. The withdrawal technique used is the